Luminescent pyrrole-based phosphaphenalene gold complexes: versatile anticancer tools with wide applicability - Fermi, Valentina; Regulska, Elzbieta; Wolfram, Anna; Weßling, Patrik; Rominger, Frank; Herold-Mende, Christel; Romero-Nieto, Carlos (Chemistry - a European journal, 2022)
Brain cancer, one of the most lethal diseases, urgently requires the discovery of novel theranostic agents. In this context, molecules based on six-membered phosphorus heterocycles - phosphaphenalenes - are especially attractive; they possess unique characteristics that allow precise chemical engineering. Herein, we demonstrate that subtle structural modifications of the phosphaphenalene-based gold(I) complexes lead to modify their electronic distribution, endow them with marked photophysical properties and enhance their efficacy against cancer. In particular, phosphaphenalene-based gold(I) complexes containing a pyrrole ring show antiproliferative properties in 14 cell lines including glioblastomas, brain metastases, meningiomas, IDH-mutant gliomas and head and neck cancers, reaching IC50 values as low as 0.73 μM. The bioactivity of this new family of drugs in combination with their photophysical properties thus offer new research possibilities for both the fundamental investigation and treatment of brain cancer.